FRACTAL ANALYSIS OF TRABECULAR BONE PATTERN IN THE MANDIBLE AS AN INDICATOR OF OSTEOPOROSIS IN WOMEN - A CLINICAL STUDY - K, Vijayalakshmi; C L, Krithika; P H, Raghuram; A, Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objectives of this study were to estimate and compare the measurement of trabecular bone pattern in the mandible of normal and osteoporotic volunteers. Methods: A 43 female volunteers were selected as osteoporotic (n=43) group and 30 as normal (n=30) group with age ranging from 25 to 60 years were enrolled based on bone mineral densitometer (BMD) in the calcaneus bone. A detailed case history followed by digital periapical radiograph was performed. The mandibular trabecular bone pattern in these volunteers was determined using Image J software, after standardizing the pixel size and locations of the region of interest for three different regions between the two groups. Statistical analysis using independent t-test and Pearson coefficient was performed. Results: Results showed a significant difference in mean BMD values between the groups (0.52 in normal and âˆ’3.22 in osteoporotic). There are no significant differences in mean fractal dimension values between the groups (0.83 in normal and 0.82 in osteoporotic). Pearson correlation coefficient shows no significant correlation between the groups at three sites (pËƒ0.001). Conclusion: Although trabecular bone microstructure on an intraoral radiograph plays a key role in defining osteoporosis, the present study did not show any significant difference in its architecture between normal and osteoporotic individuals as defined by BMD. Therefore, further studies should be performed using better-standardized resolution strategies and different estimation methods to gain more insight.